Synchrotron-based phase contrast imaging of cardiovascular tissue in mice—grating interferometry or phase propagation?. (8th November 2018) - Trachet, Bram; Lovric, Goran; Villanueva-Perez, Pablo; Aslanidou, Lydia; Ferraro, Mauro; Logghe, Gerlinde; Stergiopulos, Nikolaos; Segers, Patrick
Abstract: Synchrotron-based x-ray phase-contrast imaging allows for detailed 3D insight into the microstructure of soft tissue and is increasingly used to improve our understanding of mouse models of cardiovascular disease. Two techniques dominate the field: grating interferometry, with superior density contrast at mid to lower microscopic resolutions, and propagation-based phase contrast, facilitating high-resolution tissue imaging. The choice between these techniques depends on which features one is interested in visualizing and is thus highly sample-dependent. In this manuscript we systematically evaluate the advantages and disadvantages of grating interferometry and propagation-based phase contrast for the specific application of pre-clinical cardiovascular tissue. We scanned samples obtained from 5 different mouse models of cardiovascular disease, ranging from carotid plaques over ascending and abdominal aortic aneurysms to hypertrophic hearts. Based on our findings we discuss in detail how synchrotron-based imaging can be used to increase our understanding of the anatomy and biomechanics of cardiovascular disease in mice. We also present a flowchart that can help future users to select the best synchrotron-based phase contrast technique for their pre-clinical cardiovascular samples.